Cooperative decision-making in borderline personality disorder: insights from a preregistered study using a comprehensive economic task battery - Doppelhofer, Lisa M.; Löloff, Johanna; Neukel, Corinne; Herpertz, Sabine; Korn, Christoph W. (Borderline Personality Disorder and Emotion Dysregulation, 2025)
Social decision-making poses challenges for individuals with Borderline Personality Disorder (BPD), which can lead to maladaptive interpersonal functioning. Although previous research on cooperative decisions in BPD has produced mixed findings, studies examining different aspects of cooperative behavior suggest that individuals with BPD may specifically show reduced reactive cooperation, while their active cooperation appears similar to that of healthy individuals.
Gesehen am 29.09.2025